High‐spin Fe2+ and Fe3+ in single‐crystal aluminous bridgmanite in the lower mantle. Issue 13 (14th July 2016) - Lin, Jung‐Fu; Mao, Zhu; Yang, Jing; Liu, Jin; Xiao, Yuming; Chow, Paul; Okuchi, Takuo
Abstract: Spin and valence states of iron in single‐crystal bridgmanite (Mg0.89 Fe0.12 Al0.11 Si0.89 O3 ) are investigated using X‐ray emission and Mössbauer spectroscopies with laser annealing up to 115 GPa. The results show that Fe predominantly substitutes for Mg 2+ in the pseudo‐dodecahedral A site, in which 80% of the iron is Fe 3+ that enters the lattice via the charge‐coupled substitution with Al 3+ in the octahedral B site. The total spin momentum and hyperfine parameters indicate that these ions remain in the high‐spin state with Fe 2+ having extremely high quadrupole splitting due to lattice distortion. (Al, Fe)‐bearing bridgmanite is expected to contain mostly high‐spin, A‐site Fe 3+, together with a smaller amount of A‐site Fe 2+, that remains stable throughout the region. Even though the spin transition of B‐site Fe 3+ in bridgmanite was reported to cause changes in its elasticity at high pressures, (Fe, Al)‐bearing bridgmanite with predominantly A‐site Fe will not exhibit elastic anomalies associated with the spin transition. Key Points: Spin and valence states of Fe in bridgmanite are investigated by X‐ray emission and Mössbauer up to 115 GPa after laser annealing Fe 2+ and Fe 3+ are in the high‐spin state in the A site of bridgmanite lattice and remain stable throughout the lower mantle (Fe, Al)‐bearing bridgmanite will not exhibit elastic anomalies associated with the spin transition, in contrast to ferropericlase